Lymphocyte Proliferation Activity MTT -Test of Ethanolic Extract of Pasak Bumi Root (Eurycoma longifolia Jack) On Induced 7,12-Dimethylbenz[A] Antracene (DMBA) Female Sprague Dawley Rat - Lily Noor Falah; Sapto Yuliani (Indonesian Society for Cancer Chemoprevention, 2011)
Pasak bumi root (Eurycoma longifolia Jack) contains quasinoid. Quasinoid potentially has antitumor/anticancer, anti-parasitic, and immunostimulatory activity. The aim of this research was to study the lymphocyte proliferation activity MTT-test of ethanol extract of Eurycoma longifolia Jack root on induced by 7,12-dimethylbenz[a] antracene (DMBA) female Sprague Dawley rat. The test was done at 6 groups of 10 SD rat each. Each groups was administered orally with DMBA (Group I) dose of 20 mg/kg bw, corn oil (Group II), baseline (Group III), and ethanol extract of pasak bumi root dose 12.6; 25.2; and 50.4 mg/kg bw (Group IV,V,and VI). Ethanol extract is given for 5 weeks. At the second week five rats were sacrificed to isolate the lymphocytes of spleen then rats are injected orally with DMBA 2 times a week for 5 weeks. At the eight until twenty fourth week all groups were just administered by aquades. Measurement of spleen relative weight and isolation of the lymphocyte spleen were done at second week and the last of experiment. Lymphocyte proliferation activity were measured by MTT-reduction method. Data were analyzed statistically by analyzes of variance (anova) continued by LSD test and Kruskall Wallis continued by Mann Whitney test. The result showed that limphocyte proliferation activity MTT of ethanol extract of E. longifolia root doses of 12.6; 25.2; and 50.4 mg/kg bw for 14 days prior to DMBA-induced are 339.35 ± 8.43;61.20 ± 6.27;310.28 ± 6.81 and dose 50,4 mg/kg bw after DMBA-induced is 122.108 ± 11.426 .Keyword: E. longifolia root, spleen, lymphocyte cell, 7,12-Dimetilbenz (a) antracene (DMBA)